2021
DOI: 10.7717/peerj.11099
|View full text |Cite
|
Sign up to set email alerts
|

Subsoiling increases aggregate-associated organic carbon, dry matter, and maize yield on the North China Plain

Abstract: Background Soil degradation is one of the main problems in agricultural production and leads to decreases in soil quality and productivity. Improper farming practices speed this process and are therefore not conducive to food security. The North China Plain (NCP) is a key agricultural area that greatly influences food security in China. To explore the effects of different tillage measures on aggregate-associated organic carbon (AOC), the accumulation and transport of dry matter, and maize yield,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Cervantes et al [78] stated that after the deep plowing, the layer of the deeply plowed fields accumulated 0.4 ± 0.1 Mg SOC ha −1 yr −1 on average. In the study by Shen et al [79], subsoiling was found to increase aggregate-associated organic carbon, dry matter and maize yield on the North China Plain.…”
Section: The Influence Of Soil Management On Socmentioning
confidence: 94%
“…Cervantes et al [78] stated that after the deep plowing, the layer of the deeply plowed fields accumulated 0.4 ± 0.1 Mg SOC ha −1 yr −1 on average. In the study by Shen et al [79], subsoiling was found to increase aggregate-associated organic carbon, dry matter and maize yield on the North China Plain.…”
Section: The Influence Of Soil Management On Socmentioning
confidence: 94%
“…In Europe, a shallow working depth (5-10 cm) was recommended for wheat and barley by Arvidsson et al (2013), but 20-25 cm was also suggested for wheat and barley by Arvidsson (1998). Similar inconsistent situations were observed in Asia, Africa, South America, and Australia (Stibbe and Kafkafi 1973, Adeoye 1982, Barbosa et al 1989, Barber and Díaz 1992, Hammad and Dawelbeit 2001, Kothari et al 2003, Hemmat 2009, Berhe et al 2012, Salem et al 2015, Zeyada et al 2017, Sun et al 2019, Shen et al 2021, Gu et al 2022, the optimum tillage depth ranges from 10 cm to 50 cm for soybean, wheat, and maize under differential countries. Obviously, the optimum tillage depth was highly scattered in differential research, this is presumably largely due to the strongly site-specific effects of tillage depth on crop yields.…”
mentioning
confidence: 86%
“…The core of agricultural green development is green agricultural production, which is a production model aimed at energy conservation and emission reduction adopting green agricultural production technologies to achieve sustainable development [17]. Shen et al demonstrated that compared with conventional tillage, the use of subsoiling, no-tillage and other green agricultural production technologies [18] increased the aggregate associated organic carbon in the soil by 9.73%, effectively enhancing the carbon sequestration capacity of the soil [19]. Therefore, agricultural green development is an important support for consolidating the achievements of black land protection.…”
Section: Introductionmentioning
confidence: 99%